Utilisation of Prophylactic Mastectomy in 10 European Centres. Issue 1 (17th June 2013) - Evans, D. G. R.; Anderson, E.; Lalloo, F.; Vasen, H.; Beckmann, M.; Eccles, D.; Hodgson, S.; Møller, P.; Chang-Claude, J.; Morrison, P.; Stoppa-Lyonnet, D.; Steel, M.; et al.
Abstract : Increasingly women at high risk of breast cancer are opting for prophylactic surgery to reduce their risks. Data from 10 European centres that offer a risk counselling and screening service to women at risk show different approaches to the option of preventive surgery, although most centres adhere to a protocol including at least two risk counselling sessions and a psychological assessment. Thus far the combined centres have data on 174 women who have undergone prophylactic mastectomy with in excess of 400 women years of follow up. Operations were carried out on women with lifetime risks of 25–80%, with an average annual expected incidence rate of 1% per women. No breast cancers have occurred in this cohort. Long term follow up on an extended group of women will be necessary to truly address the risk of subsequent breast cancer and the psychological sequelae.